The Iodine Status of Women of Childbearing Age in an Iodine-repleted Area: An Epidemiological Study in Sengi Village on Merapi Mountain Area - Heri Nugroho; Tjokorda Gde Dalem Pemayun; Darmono Darmono; Banundari Rachmawati (Acta Medica Indonesiana)
Background: The low iodine content of daily water sources and repeated volcanic eruptions are expected to affect the iodine status and thyroid hormone profile of women of childbearing age in the Magelang regency. This study aimed to determine the iodine and thyroid profile among women of childbearing age. Methods: We used a cross-sectional descriptive study to learn about 140 women of reproductive age living in Sengi village from October 2017 to January 2018. We assessed the iodine level, dietary intake, and goitrogenic food consumption using food frequency questionnaire (FFQ), urinary iodine concentration (UIC), thyroid stimulating hormone (TSH) and free thyroxine (fT4), and total goiter rate (TGR). Results: The median UIC was 199.5 (126.0 – 264.0)µg/L. The TGR was 10.7% on palpation and 7.8% on ultrasound. The proportion of UIC levels below 100µg/L was 18.5%. The mean water iodine content was 2.03 ± 4.74 μg/L. The mean salt iodine level was 28.6±13.7ppm. There were only 35% who consumed salt with adequate iodine contents, and only 19.29% consumed >150µg iodine from daily dietary intake based on FFQ. The median TSH and FT4 levels were 1.72 and 1.51mIU/L. Conclusion: Women of childbearing age in Sengi Village generally had adequate iodine profiles and normal thyroid hormone levels but a considerable proportion of TGR and low UIC. The iodine contents within the freshwater source, table salt, and daily dietary intake were low. There are no significant association between Iodine status, daily goitrogen intake, daily iodine intake and salt iodine concentration